Taṭbīq Ṭarīqah bi al-Kalimāt al-Mutaqāta’ah litarqiyyah Qudrah al-Ṭullāb ‘ala Tarkīb al-Ḥurūf al-Hijā’iyyah - Nur Rahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
Vocabulary is a set of language words. Vocabulary is important in the process of developing student language. The more vocabulary the students master, the more he talks and writes. Teaching writing begins with writing letters, words and then sentences. Sometimes the mistake in word writing causes wrong meaning. Therefore, Arabic students must learn and understand it. This research was conducted at the Babun Najah boarding school where students learn vocabulary at the school. However, the researcher found mistake from students in vocabulary writing, such as installing letters on the word